PENGARUH KOMITMEN ORGANISASI, KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP TURNOVER INTENTION PADA KARYAWAN HOTEL MUTIARA MERDEKA PEKANBARU - Annisa Noviani Rachmah; Machasin '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
satisfaction of job and organizational culture to turnover intention employees At Hotel Mutiara Merdeka Pekanbaru. This Research Obyek is employees at Hotel Mutiara Merdeka Pekanbaru. As for becoming population in this research HotelMutiara Merdeka Pekanbaru which is amount 130 people. While method intake of sample conducted by using formula of Slovin so that the amount of sample obtained by counted 98 people. In analyse data to data which have been got, writer use method equation of doubled linear regression, by using program of SPSS (Statistical Product and Service Solution). From result of examination which have been conducted, test of regression by simultan (uji-F) and by parsial (uji-T) indicated that correctness of commitment organizational, satisfaction ofwork, and organization culture have an effect on to intention turnover at Mutiara Merdeka Hotel Pekanbaru, organizational commitment have an effect on to intention turnover at Mutiara Merdeka Hotel Pekanbaru, satisfaction of work have an effect on to intention turnover at Mutiara Merdeka Hotel Pekanbaru,cultural of organization have an effect on to intention turnover at Mutiara Merdeka Hotel Pekanbaru.Keywords: Commitment, Satisfaction, Culture, and Turnover Intention